(untitled) - Agrawal, Rattan Lal (Hoboken, N.J., 1998)
This text explores the fundamentals of plant breeding and hybrid seed production. It examines issues including male sterility, composite and synthetic varieties and disease resistance breeding.
Keywords: Plant breeding,Cây trồng; Công nghệ di truyền